Myoelectrical Manifestation of Fatigue Less Prominent in Patients with Cancer Related Fatigue - Kisiel-Sajewicz, Katarzyna (Public Library of Science, 2013)
PURPOSE: A lack of fatigue-related muscle contractile property changes at time of perceived physical exhaustion and greater central than peripheral fatigue detected by twitch interpolation technique have recently been reported in cancer survivors with fatigue symptoms. Based on these observations, it was hypothesized that compared to healthy people, myoelectrical manifestation of fatigue in the performing muscles would be less significant in these individuals while sustaining a prolonged motor task to self-perceived exhaustion (SPE) since their central fatigue was more prominent. The purpose of this study was to test this hypothesis by examining electromyographic (EMG) signal changes during fatiguing muscle performance. METHODS: Twelve individuals who had advanced solid cancer and cancer-related fatigue (CRF), and 12 age- and gender-matched healthy controls performed a sustained elbow flexion at 30% maximal voluntary contraction till SPE. Amplitude and mean power frequency (MPF) of EMG signals of the biceps brachii, brachioradialis, and triceps brachii muscles were evaluated when the individuals experienced minimal, moderate, and severe fatigue. RESULTS: CRF patients perceived physical “exhaustion” significantly sooner than the controls. The myoelectrical manifestation of muscular fatigue assessed by EMG amplitude and MPF was less significant in CRF than controls. The lower MPF even at minimal fatigue stage in CRF may indicate pathophysiologic condition of the muscle. CONCLUSIONS: CRF patients experience less myoelectrical manifestation of muscle fatigue than healthy individuals near the time of SPE. The data suggest that central nervous system fatigue plays a more important role in limiting endurance-type of motor performance in patients with CRF.